Using Natural Resources in an Optimal Way - World Bank (Washington, DC, 2014)
To ensure sustainable and optimal use of its common property natural resources, Mexico will need to strengthen its focus on enhancing stewardship in three key sectors-forests, water, and energy resources. The key objectives include the following: 1) identifying options that would contribute to Mexico's climate agenda and build social resilience through forest management; 2) ensuring economically efficient and environmentally and socially sustainable water management to promote 'green' growth in the context of water scarcity and climate uncertainty; and 3) assessing the impacts of declining oil and gas reserves and the role of renewable energy as an alternative and cleaner source. Forests can play an important role in mitigating and adapting to climate change. Reducing Emissions from Deforestation and Forest Degradation (REDD+) and other forest-related activities could account for almost 20 percent of reductions in greenhouse gas emissions that Mexico could achieve by 2030. Although much remains to be done, Mexico has become a global leader in forest management. Allocation of resources among the various programs is not optimal. Reforestation efforts have obtained modest results despite receiving 38 percent of Mexico's forest investments in 2011 (US$486 million). The capacity to monitor investments is lagging compared with the scale of the programs.